PENGARUH LEVERAGE FINANCIAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA) - Hartawati, Sri Indira (Jurnal Ekonomi Balance, 2013)
This study aims to examine and analyze the effect of partially or simultaneously financial leverage and dividend policy on firm value in manufacturing companies on the Indonesian stock exchange. Data collection uses secondary data using purposive sampling technique. The population in this study is the automotive sub-sector manufacturing companies and components listed on the Indonesia stock exchange during the 2014-2016 period of 15 companies, while the samples taken were the number of observations for 3 years (2014-2016) with the number of companies observing 12 obtained were analyzed using multiple linear regression analysis. The results show that all hypotheses have a significant effect based on the t test and F test. This means that both partially and simultaneously financial leverage and dividend policy have a significant effect on firm value in manufacturing companies on the Indonesian stock exchange.